1996
DOI: 10.1007/bf01771236
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fertilizer and sewage sludge compost on yield and heavy metal accumulation by lettuce grown in urban soils

Abstract: Previous research has demonstrated that many urban soils are enriched in Pb, Cd and Zn. Culture of vegetable crops in these soils could allow transfer of potentially toxic metals to foods. 'Tanya' lettuce (Lactuca sativa L.) was grown in pots of five urban garden soils and one control agricultural soil to assess the effect of urban-soil metal enrichment, and the effect of soil amendments, on heavy metal uptake by garden vegetables. The amendments included NPK fertilizer, limestone, Ca(H2PO4)2, and two rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 41 publications
(66 reference statements)
1
34
0
1
Order By: Relevance
“…Metal contamination of garden soils may be widespread in urban areas due to past industrial activity and the use of fossil fuels (Chronopoulos et al, 1997;Sánchez-Camazano et al, 1994;Sterrett et al, 1996;van Lune, 1987;Wong, 1996). Heavy metals may enter the human body through inhalation of dust, direct ingestion of soil, and consumption of food plants grown in metal-contaminated soil (Cambra et al, 1999;Dudka and Miller, 1999;Hawley, 1985).…”
Section: Hazardous Effects Of Heavy Metals On Human Healthmentioning
confidence: 99%
“…Metal contamination of garden soils may be widespread in urban areas due to past industrial activity and the use of fossil fuels (Chronopoulos et al, 1997;Sánchez-Camazano et al, 1994;Sterrett et al, 1996;van Lune, 1987;Wong, 1996). Heavy metals may enter the human body through inhalation of dust, direct ingestion of soil, and consumption of food plants grown in metal-contaminated soil (Cambra et al, 1999;Dudka and Miller, 1999;Hawley, 1985).…”
Section: Hazardous Effects Of Heavy Metals On Human Healthmentioning
confidence: 99%
“…Metal contamination of garden soils may be widespread in urban areas due to past industrial activity and the use of fossil fuels (Chronopoulos et al 1997;SanchezCámazano et al 1994;Sterrett et al 1996;van Lune 1987;Wong 1996). Heavy metals may enter the human body through inhalation of dust, direct ingestion of soil, and consumption of food plants grown in metal-contaminated soil (Cambra et al 1999;Dudka and Miller 1999;Hawley 1985).…”
mentioning
confidence: 99%
“…Metal contamination of garden soils may be widespread in urban areas due to continuous industrial activities and the use of fossil fuels (Chronopoulos et al, 1997). Several studies have shown that the concentrations of heavy metals in vegetation and natural rodent populations are generally correlated with environmental pollution (Schleich et al, 2010;Hawley, 1985;Sánchez-Camazano et al, 1994;Sterrett et al, 1996;Van Lune, 1987). Heavy metals which usually got transferred unto man and have highly adverse effects are lead, cadmium, copper, chromium, selenium and mercury (Wong, 1996).…”
Section: Introductionmentioning
confidence: 99%